The Effects of Glucagon-Like Peptide-1 Agonist Therapy (Semaglutide and Tirzepatide) on Metabolic and Hormonal Parameters in Men with Obesity and Insulin Resistance - Jumayev Mukhammadali Jakhongirovich (Global Scientific Publishing, 2026)
In recent years, obesity and insulin resistance have become increasingly prevalent among men and are considered key pathogenetic factors in the development of metabolic syndrome, type 2 diabetes mellitus, and hormonal imbalance. In such conditions, glucagon-like peptide-1 (GLP-1) receptor agonists—semaglutide and the dual GIP/GLP-1 agonist tirzepatide—have been recognized as effective pharmacological treatment options. This article analyzes the effects of these therapies on metabolic and hormonal parameters in men with obesity and insulin resistance. The results of clinical studies demonstrate that the use of semaglutide and tirzepatide is associated with significant weight reduction, improved insulin sensitivity, stabilization of glycemic control, and optimization of lipid metabolism. Moreover, weight loss and reduction of visceral adipose tissue contribute to the improvement of hormonal balance in men, particularly through an indirect increase in testosterone levels, reduction of leptin resistance, and enhancement of adiponectin secretion. The dual mechanism of action of tirzepatide further enhances its metabolic efficacy, providing superior clinical outcomes in patients with severe insulin resistance. This article highlights the role of GLP-1 agonists in the comprehensive management of metabolic and endocrine disorders in men and substantiates their clinical relevance.
Keywords: obesity; insulin resistance; GLP-1 receptor agonists; semaglutide